Uwarunkowania przeciwdziałania zjawisku dyskryminacji osób niskich w przestrzeni publicznej i projektowaniu użytkowym – w perspektywie stanowienia i stosowania prawa - Przystaś, Aleksandra (Studia Prawa Publicznego, 2023)
The study is devoted to legal and factual conditions of the social situation of short people, in particular, in terms of actual and potential areas of risk of discrimination based on height, that does not correspond to the average in a given society. The article indicates the extent of height discrimination, referred to as heightism, and deals with social behaviours that can be classified as unfair and violating the subjective rights of a group of people who are characterized by their below-average height compared to the social average. This manifests itself in various aspects, including communication practices established in society, such as the infantilization of short people, which in turn negatively affects other spheres of these people’s social functioning. Moreover, discrimination in the social sphere is also evident in the employment opportunities offered to people of short stature – they are perceived as less experienced and less competent. It is also a problem that employers set requirements regarding the parameters of job applicants in situations where these is not actually necessary for the proper performance of the tasks required. What’s more, there is discrimination hindering, and sometimes severely limiting, the possibility of using public utility facilities (functioning in the public sphere), and utility items referring to the private sphere. Based on the analysis of case-law related to the situation of people of short stature and also anti-discriminatory solutions functioning in other countries, specific remedies for discrimination against short people have been proposed, which should be applied both in Polish legislation and in the implementation of existing law. The idea here is to expand the guarantee norms contained in the Polish constitution so that they explicitly prohibit discrimination on the grounds of height.